MEMPERTIMBANGKAN ANALISIS GENDER DALAM DISKURSUS FIKIH: SEBUAH UPAYA BAGI KONTEKSTUALISASI FIKIH ISLAM - Darwin Panessai; Ubay Harun; Hayyun Nur (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2021)
As many studies have been done on fiqh discourse from a feminist perspective, most of them conclude that in terms of the ontological position and sociological role of women are spoken, fiqh books in the classic era and the post-era have the same dominant ideas that are the trend towards placing women in an instrumental rather than a substantial position. Therefore, the study of fiqh using gender analysis as an analytical knife is an urgent alternative study to be carried out immediately.